Identifying plasmodium falciparum EBA-175 homologue sequences that specifically bind to human erythrocytes (2004)
Erythrocyte binding antigen-160 (EBA-160) protein is a Plasmodium falciparum antigen homologue from the erythrocyte binding protein family (EBP). It has been shown that the EBP family plays a role in parasite binding to the erythrocyte surface. The EBA-160 sequence has been chemically synthesised in seventy 20-mer sequential peptides covering the entire 3D7 protein strain, each of which was tested in erythrocyte binding assays to identify possible EBA-160 functional regions. Five EBA-160 high activity binding peptides (HABPs) specifically binding to erythrocytes with high affinity were identified. Dissociation constants lay between 200 and 460 nM and Hill coefficients between 1.5 and 2.3. Erythrocyte membrane protein binding peptide cross-linking assays using SDS–PAGE showed that these peptides bound specifically to 12, 28, and 44 kDa erythrocyte membrane proteins. The nature of these receptor sites was studied in peptide binding assays using enzyme-treated erythrocytes. HABPs were able to block merozoite in vitro invasion of erythrocytes. HABPs’ potential as anti-malarial vaccine candidates is also discussed.